Assessing the information needs on production process within the construction industry - Santos, Aguinaldo dos (InfoDesign, 2005)
The present paper analyses the usage level of one of the core heuristic for increasing transparency in production systems: incorporating information into the production process. This research brings a different perspective to the design information community by presenting the point of view of production management. The data collection was carried out within six case studies in Brazil and England and adopted a patternmatching analytical approach. The empirical evidence showed that construction makes very limited use of such an approach despite the problems caused by the lack of information among the workforce. Further developments have to be carried, aimed at the creative installation of information in equipment and materials in order to make the distribution channels more compatible with the continuous movement of construction workstations.